Indigeneous microorganism and red wiggler worm (eiseniafetida) as composting agents for pruned oil palm leaves / Norhaslinda Arun, Wan Hanisah Wan Ismail and Nor Azian Iskandar - Arun, Norhaslinda; Wan Ismail, Wan Hanisah; Iskandar, Nor Azian (2011)
The study was conducted to compare the rates of composting of oil palm leaves through vermicomposting and Indigenous Microorganism (IMO). Three treatments with three replications were made, which consist of oil palm leaves with worms, oil palm leaves with IMO, and oil palm leaves without composting agent serve as control. Each replication was treated with 3kg of worm and 3kg of1MO Data was collected within a period of 12 weeks. Results revealed that composting with worm proceeded at a faster rate with greater volume as compared to those treated with IMO and the control boxes. Generally, there were no significant differences in compost quality among the three treatments, with the exception of phosphorus content which was observed to be slightly higher in the worm-composted materials